Correlation between serum vitamin D3 levels and blood pressure in patients with essential hypertension and normotensive individuals - Patil, Divya V.; Dutta, Tarun Kumar (International Journal of Advances in Medicine, 2020)
Background: Vitamin D, a fat-soluble vitamin is produced when ultraviolet rays from sunlight strike the skin. Literature data supports, there is a relationship between low vitamin D and pathogenesis of cardiovascular diseases and arterial hypertension. It had been seen that lower circulating 25(OH)D levels were associated with higher blood pressures. Aim was to study the correlation between serum vitamin D3 levels and blood pressure in patients with essential hypertension and normotensive individuals. Methods: An observational study was conducted on 60 individuals in the OPD at MGMCRI between January 2018 and December 2018. Based on history and blood pressure values (JNC 7), the population was divided into cases and controls in accordance with the age and sex. Serum Vitamin D levels were measured by chemiluminescence assay and classified into deficiency (<20ng/ml), insufficiency (20-30ng/ml) and sufficiency (30-100ng/ml). Statistical analysis was done using independent t test, one way ANOVA and correlation. Results: Among the hypertensive individuals, 90% were Vitamin D deficient and 10% had insufficiency. The mean Serum Vitamin D level in essential hypertension was 14.6±4.401 (p value <0.001). Serum Vitamin D levels were affected significantly by increasing BMI (p value <0.001) and less sunlight exposure (p value <0.001) among both cases and controls. There was also a significant negative correlation between serum vitamin D levels and systolic blood pressure (p <0.001). Conclusions: Isolated systolic hypertension was associated with lower serum Vitamin D levels. Obesity and reduced sunlight exposure are factors associated with lower serum Vitamin D levels.